TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK PEMBERIAN UPAH BURUH PEMELIHARA SAPI DI DESA TENGGEER KULON KAB. TUBAN - Fitriyah, Lailatul; Fahrullah, (Universitas Negeri Surabaya, 2022)
Muamalah activity is one of the activities prescribed by the Islamic religion, namelywages or cooperation. As social beings, in carrying out muamalah activities, we definitely need the help of other humans. Wages in fiqh muamalah are known as Ijarah. The practice of wage labor for cattle is a collaboration between the two parties, namely the owner of the cow and the laborer. The practice of wage labor for cattle is often carried out by the people of Tengger Kulon Village - Tuban as a side profession to meet their daily needs. This study uses a qualitative descriptive method with the aim ofknowing the review of Islamic law on the wage mechanism for cattle keeping workers in Tengger Kulon Village - Tuban. Based on the results of the study, it shows that the wage transactions for cattle workers in Tengger Kulon Village – Tuban are not fully in accordance with Islamic law which refers to the Qur'an and hadith because there are disadvantages that contain elements of dzulm because they have not achieved justice.